Lateral Periodontal Cyst Treated with Enucleation and Guided Bone Regeneration: A Report of a Case and a Review of Pertinent Literature - Sundar Ramalingam; Yasser Fahad Alrayyes; Khalid Buayjan Almutairi; Ibrahim O. Bello (Case Reports in Dentistry)
Lateral periodontal cyst (LPC) is an uncommon developmental odontogenic cyst arising on the lateral surface of tooth roots. Commonly reported in mandibular canine-premolar or maxillary anterior regions, it presents as a well-circumscribed or tear drop-shaped radiolucency with a sclerotic border. Associated teeth are asymptomatic and vital, and roots may be displaced without resorption. Histopathologically, cystic lining resembles reduced enamel epithelium along with glycogen-rich clear cells and epithelial plaques. Unilateral variant of LPC has low recurrence and is managed by enucleation. A 43-year-old male patient reported with asymptomatic swelling in the left mandibular canine and first premolar region. Both teeth were vital, and radiographs revealed well-circumscribed radiolucency between the roots. Following consent, surgical enucleation and guided bone regeneration (GBR) with xenograft and resorbable collagen membrane were done under local anesthesia. The immediate postoperative period was uneventful, and complete bone fill of cystic cavity and healing of periodontal tissues was observed after a one-year follow-up. Histopathologic examination confirmed the diagnosis. LPC should be a differential diagnosis in cystic lesions lateral to the surface of a tooth and without any associated inflammation. Based on this case report, unicystic LPC can be successfully managed through surgical enucleation with GBR for better periodontal healing.